Pengaruh Promosi dan Lokasi Usaha Terhadap Keputusan Pembelian pada Beach And Beats Cafe Pandan Kabupaten Tapanuli Tengah - Rizky Ezra Saputra Sitanggang (EBISMA : Jurnal Ekonomi, Bisnis, Manajemen dan Akuntansi, 2026)
This study aims to analyze the effect of promotion and business location on purchasing decisions at Beach and Beats Cafe Pandan, Central Tapanuli Regency. The research employed a quantitative approach using descriptive and verificative methods. The sample consisted of 75 respondents who were consumers of the cafe, and data were collected through questionnaire distribution. Data analysis was conducted using t-tests and F-tests. The results indicate that promotion has a positive and significant effect on purchasing decisions (t = 4.498; p < 0.05). Similarly, business location also has a positive and significant effect on purchasing decisions (t = 4.197; p < 0.05). Simultaneously, promotion and business location have a positive and significant effect on purchasing decisions (F = 55.211; p < 0.05). These findings suggest that improving promotional strategies and selecting a strategic business location can enhance consumers’ purchasing decisions.